Chlorine-induced stress corrosion cracking of single crystal superalloys at 550 °C - Duarte Martinez, Fabian; Dawson, Karl; Tatlock, Gordon J.; Leggett, Jonathan; Gibson, Grant J.; Mason-Flucke, Julian C.; Nicholls, John R.; Syed, Adnan U.; Morar, Nicolau I.; Gray, Simon (Springer, 2024)
This study has investigated the effect of NaCl and different gaseous environments on the stress corrosion cracking susceptibility of CMSX-4 at 550 °C. The presence of SOx leads to the rapid dissociation of NaCl into Na2SO4 and the release Cl2 and HCl, which then trigger an active oxidation mechanism and stress corrosion cracking. The incubation time for crack initiation at 690 MPa and in the presence of a sulphur containing environment is 10 min. A working hypothesis is that stress corrosion cracking occurs due to the hydrogen released at the oxide/alloy interface when metal chlorides are formed; however, this hypothesis needs to be further explored.
Keywords: Stress corrosion cracking; CMSX-4; Hydrogen